Education and Social Innovation: The Youth Uncensored Project—A Case Study of Youth Participatory Research and Cultural Democracy in Action - Conrad, Diane H (Canadian Journal of Education/Revue canadienne de l'éducation, 2015)
This article discusses social innovation in education informed by arts-based and Indigenous ways of knowing. I use the term Indigenous to refer to First Peoples’ and their wisdom traditions from places around the world and the term Aboriginal to refer to the diverse First Nations, Métis, and Inuit peoples of Canada. The article looks at the ethical imperative for doing socially innovative work, and examines practices with potential for embedding social innovation in educational scholarship, including experiential and relational educational approaches, such as community-service learning and restorative justice; participatory action research as an allied research approach; and community arts framed as cultural democracy. It describes a research project with street-involved youth as a case study for research that moves toward social innovation through the Government of Canada Policy Research Initiative’s five steps involved in a co-creative social innovation project.